Aqueous solution of mPEG modified polyester material as well as preparation method and application of aqueous solution

The nanomicrobial aqueous solution was prepared by mPEG modification of polyester material and the addition of phosphate at a specific concentration was solved, which solved the problem of agglomeration after redissolution of the polyester material, and achieved the use of finer injection needles and better histocompatibility.

CN119455100APending Publication Date: 2025-02-18SICHUAN HUIYU YUEYING MEDICAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411608485.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-10-28
Filing Date
2024-11-12
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Existing polyester materials are prone to agglomeration after redissolution, resulting in adverse reactions such as nodules, granulomas and inflammation at the injection site. The high viscosity dispersion medium makes production difficult, and thinner injection needles cannot be used to relieve pain.

Method used

The nano micelle aqueous solution is prepared by using mPEG modified polyester material. By adding a specific concentration of phosphate, the particle size and distribution are controlled, the viscosity is reduced, and histocompatibility is improved.

Benefits of technology

Good dispersion and uniformity of nano micelle aqueous solution is achieved, the adverse reaction rate after injection is reduced, and the use of thinner injection needles is allowed to reduce pain, and histocompatibility and collagen regeneration effect is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455100A_ABST
    Figure CN119455100A_ABST
Patent Text Reader

Abstract

The invention relates to an aqueous solution of an mPEG modified polyester material as well as a preparation method and application thereof, and belongs to the technical field of materials. The invention provides an aqueous solution of an mPEG modified polyester material. The polyester material is formed by polymerizing at least one monomer of L-lactide, epsilon-caprolactone, glycolide and p-dioxanone. The mPEG modified polyester material is a diblock copolymer or a triblock copolymer; the content of the mPEG modified polyester material in the aqueous solution is 10-28% w / w, and the aqueous solution contains phosphate with the concentration of 9.86 mmol / L to 0.12 mol / L. By adding phosphate with a specific concentration, the prepared nano-micelle aqueous solution has the advantages of small particle size, uniform particle size distribution, high stability, good dispersibility and ductility after injection, good histocompatibility, good skin filling and collagen regeneration effects, low incidence rate of adverse reactions and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an aqueous solution of an mPEG-modified polyester material and a preparation method and application thereof, belonging to the technical field of materials. Background Art

[0002] Polyester materials have been used in the field of medical cosmetic skin filling for many years due to their good biocompatibility and safety. The earliest polyester skin filling products approved by the FDA for use in AIDS patients It is used to improve facial defects of AIDS patients and later expanded to normal people. However, the existing polyester products are easy to agglomerate after reconstitution, resulting in needle blockage and uneven particle distribution, causing nodules, granulomas and strong inflammation at the injection site.

[0003] Chinese patent CN 115282337 A discloses a polycaprolactone microsphere pre-dispersed composition and a method for preparing a polycaprolactone injectable gel therefrom. In clinical use, injectable gels are more convenient and less risky than injection after reconstitution. However, the patent uses sodium carboxymethylcellulose gel to disperse and stabilize polycaprolactone microspheres, but the high viscosity of sodium carboxymethylcellulose gel makes it difficult to stir and disperse the microspheres evenly and fill the microspheres during production, increases the product's injection force, and cannot use a thinner injection needle to reduce the pain and impact of the injection.

[0004] In addition, existing polyester products often have defects such as poor tissue compatibility, easy formation of inclusions, and easy to cause scar hyperplasia in the process of promoting collagen regeneration. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention aims to provide an aqueous solution of mPEG-modified polyester material and a preparation method and use thereof.

[0006] The present invention provides an aqueous solution of an mPEG-modified polyester material, wherein the polyester material is formed by polymerization of at least one monomer selected from the group consisting of L-lactide, ε-caprolactone, glycolide, and p-dioxanone; the mPEG-modified polyester material is a diblock copolymer or a triblock copolymer; the content of the mPEG-modified polyester material in the aqueous solution is 10 to 28% w / w, and the aqueous solution contains phosphate at a concentration of 9.86 mmol / L to 0.12 mol / L.

[0007] Furthermore, the aqueous solution contains phosphate at a concentration of 9.86 mmol / L or 0.12 mol / L.

[0008] Furthermore, the phosphate consists of monohydrogen phosphate and dihydrogen phosphate, wherein the molar ratio of monohydrogen phosphate: dihydrogen phosphate is 1:(0.19-1.67).

[0009] Preferably, the molar ratio of monohydrogen phosphate:dihydrogen phosphate is 4.6:1 or 1:1.

[0010] Furthermore, the monohydrogen phosphate is at least one of disodium hydrogen phosphate and dipotassium hydrogen phosphate; and / or the dihydrogen phosphate is at least one of sodium dihydrogen phosphate and potassium dihydrogen phosphate.

[0011] Further, the phosphate consists of 0.06 mol / L disodium hydrogen phosphate and 0.06 mol / L sodium dihydrogen phosphate, or consists of 8.1 mmol / L disodium hydrogen phosphate and 1.76 mmol / L potassium dihydrogen phosphate.

[0012] According to some specific embodiments of the present invention, when the phosphate is potassium salt, the potassium ion concentration in the aqueous solution is controlled at 3.5-5.5 mmol / L.

[0013] Furthermore, the content of the mPEG modified polyester material in the aqueous solution is 20-28% w / w.

[0014] Preferably, the content of the mPEG-modified polyester material in the aqueous solution is 20-25% w / w.

[0015] Furthermore, the mPEG-modified polyester material in the aqueous solution is a nano-micelle.

[0016] Furthermore, the particle size D50 of the nano micelles is 10 to 500 nm.

[0017] Preferably, the particle size D50 of the nanomicelles is 100 nm to 250 nm.

[0018] Furthermore, the particle size distribution PDI of the nano micelles is 0.05 to 0.40.

[0019] Preferably, the particle size distribution PDI of the nanomicelles is 0.05 to 0.30.

[0020] Furthermore, the pH value of the aqueous solution is 5-8.

[0021] Preferably, the pH value of the aqueous solution is 6.7-7.3.

[0022] Furthermore, the viscosity of the aqueous solution is 5 to 3000 mPa. . S.

[0023] Preferably, the viscosity of the aqueous solution is 5 to 1000 mPa. . S.

[0024] Preferably, the viscosity of the aqueous solution is 50 to 1000 mPa. S.

[0025] In the present invention, the lower the viscosity of the aqueous solution, the better the diffusibility.

[0026] Furthermore, the osmotic pressure of the aqueous solution is 200-450 mOsm / kg.

[0027] Preferably, the osmotic pressure of the aqueous solution is 300-400 mOsm / kg.

[0028] Furthermore, the aqueous solution also contains an osmotic pressure regulator.

[0029] Preferably, the osmotic pressure regulator is selected from at least one of sodium chloride, potassium chloride and glycerol.

[0030] Furthermore, the mPEG-modified polyester material is selected from at least one of mPEG-b-PLLA, mPEG-b-PCL, mPEG-b-PPDO, mPEG-b-PCLA, and mPEG-b-PLGA.

[0031] Furthermore, the molecular weight of mPEG in the mPEG-modified polyester material is 500 to 20,000 Daltons.

[0032] Preferably, the molecular weight of mPEG in the mPEG-modified polyester material is 1900 to 10000 Daltons.

[0033] Preferably, the molecular weight of mPEG in the mPEG-modified polyester material is 1900-5000 Daltons.

[0034] Furthermore, the mass percentage of mPEG in the mPEG-modified polyester material is 5% to 50%.

[0035] Preferably, the mass percentage of mPEG in the mPEG-modified polyester material is 7% to 26%.

[0036] Furthermore, the aqueous solution is in the form of an injection.

[0037] According to some preferred embodiments, the present invention provides an aqueous solution of an mPEG-modified polyester material for collagen regeneration, wherein the mPEG-modified polyester material is selected from at least one of mPEG-b-PCL and mPEG-b-PCLA; the content of the mPEG-modified polyester material in the aqueous solution is 20 to 28% w / w, and contains phosphate at a concentration of 9.86 mmol / L to 0.12 mol / L; the phosphate is composed of monohydrogen phosphate and dihydrogen phosphate, wherein the molar ratio of monohydrogen phosphate: dihydrogen phosphate is 1:(0.19 to 1.67).

[0038] The invention also provides use of the aqueous solution in preparing tissue repair products.

[0039] The invention also provides use of the aqueous solution in preparing skin filling products.

[0040] The invention also provides use of the aqueous solution in preparing collagen regeneration products.

[0041] The invention also provides a method for preparing the aqueous solution, which adopts an organic solvent volatilization method.

[0042] Furthermore, the preparation method comprises the following steps: a. taking the mPEG modified polyester material, adding an organic solvent to dissolve it, adding water and the phosphate, and mixing them evenly; b. removing the organic solvent.

[0043] Furthermore, the mass volume ratio of the mPEG-modified polyester material: the organic solvent in step a is 15 g: 100 mL.

[0044] Furthermore, in step a, the volume ratio of organic solvent to water is (3-5):1.

[0045] Preferably, in step a, the volume ratio of organic solvent to water is 100:33.3.

[0046] Furthermore, in step b, the organic solvent is evaporated at 15 to 25° C. and the pressure is controlled at -0.07 to -0.09 MPa.

[0047] Preferably, in step b, the organic solvent is evaporated at 20° C. and the pressure is controlled at -0.09 MPa.

[0048] Furthermore, the organic solvent is selected from at least one of acetone, tetrahydrofuran and dichloromethane.

[0049] Furthermore, the preparation method further comprises step c: adding water and the phosphate until the mPEG-modified polyester material in the aqueous solution reaches a desired concentration.

[0050] According to some specific embodiments of the present invention, in step a and / or step c, water and the phosphate are added in the form of a phosphate aqueous solution, wherein the pH of the phosphate aqueous solution is 6.6-7.5.

[0051] The present invention provides an aqueous solution of mPEG-modified polyester material, which has at least the following beneficial technical effects:

[0052] 1. Compared with microsphere products, the nano-micelle aqueous solution of the present invention has better dispersibility and uniformity, and can directly form a uniform solution without the need for a high-viscosity dispersion medium. It can reduce the adverse reaction rate after injection caused by uneven dispersion and sedimentation of microspheres, improve the difficulty of injection caused by the particle size of microspheres, and select a thinner injection needle to reduce the pain of injection and provide injection comfort. Specifically, the experimental results show that the product of the present invention can be injected with a 30G or even thinner needle, which effectively reduces the pain of injection. Under the same conditions, compared with microsphere products, the syringe handle of the product of the present invention has a small pushing force, and there is no clogging of the injection needle during the injection process.

[0053] 2. The mPEG-modified polyester material of the present invention improves the hydrophilicity and tissue compatibility of the nanomicelles and prevents the nanomicelles from being phagocytosed by phagocytes.

[0054] 3. By adding a specific concentration of phosphate, the nanomicelle aqueous solution prepared by the present invention has the advantages of small particle size, uniform particle size distribution, high stability, good dispersibility and ductility after injection, good tissue compatibility, good skin filling and collagen regeneration effects, and low incidence of adverse reactions. BRIEF DESCRIPTION OF THE DRAWINGS

[0055] Figure 1 TEM image of the sample prepared in Example 4;

[0056] Figure 2 This is an anatomical diagram of the animal skin tissue in Experimental Example 4;

[0057] Figure 3 This is the HE staining image in Experimental Example 4;

[0058] Figure 4 It is the Masson staining picture in Experimental Example 4;

[0059] Figure 5 This is an anatomical diagram of the animal skin tissue after the sample of Comparative Example 2 was implanted in Experimental Example 5;

[0060] Figure 6 This is an anatomical diagram of the animal skin tissue after the sample of Example 7 was implanted in Experimental Example 5;

[0061] Figure 7 This is an anatomical diagram of the animal skin tissue after injection of each experimental sample in Experimental Example 6;

[0062] Figure 8 This is a diagram of tissue thickness measurement after injection of PBS solution in Experimental Example 6;

[0063] Fig. 9 This is a diagram showing the tissue thickness measurement after the sample of Example 7 was implanted in Test Example 6;

[0064] Fig.10This is a diagram showing the tissue thickness measurement after the sample of Example 8 was implanted in Experimental Example 6;

[0065] Fig.11 This is a diagram of tissue thickness measurement after implantation of the sample of Example 9 in Experimental Example 6;

[0066] Fig.12 This is a diagram of tissue thickness measurement after implantation of the sample of Example 10 in Experimental Example 6. DETAILED DESCRIPTION

[0067] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0068] In the present invention, polyethylene glycol monomethyl ether is abbreviated as mPEG, poly L-lactic acid (poly L-lactide) is abbreviated as PLLA, polycaprolactone is abbreviated as PCL, polydioxanone is abbreviated as PPDO, caprolactone lactide copolymer is abbreviated as PCLA, lactide-glycolide copolymer is abbreviated as PLGA, polyethylene glycol monomethyl ether-poly L-lactic acid is abbreviated as mPEG-b-PLLA, polyethylene glycol monomethyl ether-polycaprolactone is abbreviated as mPEG-b-PCL, polyethylene glycol monomethyl ether-polydioxanone is abbreviated as mPEG-b-PPDO, polyethylene glycol monomethyl ether-polycaprolactone lactide is abbreviated as mPEG-b-PCLA, polyethylene glycol monomethyl ether-lactide-glycolide copolymer is abbreviated as mPEG-b-PLGA, polyvinyl alcohol is abbreviated as PVA, and the uniformity of particle size distribution is represented by PDI.

[0069] Example 1 Preparation of the polymer mPEG-b-PCLA of the present invention

[0070] 1000g of polyethylene glycol monomethyl ether (mPEG, molecular weight 1900 Dalton) was added to a 5L three-necked round-bottom flask equipped with mechanical stirring and vacuum degassing, and heated to 130°C in an oil bath. After the temperature reached 130°C, vacuum degassing was performed for 30 minutes using a vacuum aspirator to remove moisture, and the vacuum degassing was stopped. Then 5890g of ε-CL (ε-CL was activated before use) was added to the round-bottom flask. Molecular sieve to remove water for 48h to remove trace water in caprolactone), 2570g L-lactide, when the material is completely melted (i.e., m ε-CL :m L-LA=7:3), add 1.6g of stannous isooctanoate to the reaction system, stir mechanically for 24h and then stop the reaction to obtain a crude block copolymer mPEG-b-PCLA. The crude product was dissolved in dichloromethane and precipitated in anhydrous ethanol with stirring, the solid precipitate was collected, and the solid precipitate was placed at 40°C and dried in vacuum for 48h to obtain the product. The mass proportion of mPEG was 7% according to H-NMR analysis.

[0071] By adjusting the input amount of mPEG, polymer products with different mPEG contents can be prepared.

[0072] Example 2 Preparation of the polymer mPEG-b-PCL of the present invention

[0073] Polyethylene glycol monomethyl ether (mPEG, molecular weight 5000 Dalton) was placed in a vacuum oven at 80°C and dried overnight to remove moisture, and then stored in a desiccator; Molecular sieves were used to dry ε-caprolactone for 48 hours to remove trace amounts of water in the caprolactone. 1000 g of dried mPEG and 3000 g of dried ε-caprolactone were placed in a single-necked flask, sealed, heated to 130°C, 6 g of stannous isooctanoate was added to the reaction system, and the reaction was stopped after stirring for 24 hours. The crude product was dissolved in dichloromethane and precipitated in ether to obtain a solid precipitate. The solid precipitate was washed with a small amount of methanol to remove unreacted mPEG. The solid precipitate was collected and placed in a vacuum dryer at 40°C for 24 hours to obtain a copolymer. The mass proportion of mPEG was 26% according to H-NMR analysis.

[0074] By adjusting the input amount of mPEG, polymer products with different mPEG contents can be prepared.

[0075] Example 3 Preparation of mPEG-b-PCLA Nanomicelle Aqueous Solution of the Present Invention

[0076] Take 1.5g of the product mPEG-b-PCLA in Example 1 and dissolve it in 10mL of acetone (oil phase), and add PBS solution (water phase, the amount of water phase added is calculated according to the oil-water ratio in Table 1, wherein the composition and concentration of PBS solution are: sodium chloride: 136.89mmol / L, potassium chloride: 2.67mmol / L, disodium hydrogen phosphate: 8.1mmol / L, potassium dihydrogen phosphate: 1.76mmol / L) under stirring. At 15-25°C, control the pressure -0.07 to -0.09MPa until the acetone residue is no more than 0.5% (according to the Chinese Pharmacopoeia 2020 Edition Part IV 0861). Add PBS solution until the total amount of the aqueous phase is 10mL, and the target product is obtained: a uniform particle size and a content of about 13% w / w (the content is measured by the drying loss method) of mPEG-b-PCLA nanomicelle aqueous solution. The specific process parameters and the corresponding particle size and particle size distribution test data are as follows:

[0077] Table 1

[0078] Oil:water volume ratio PBS supplement amount Decompression temperature Reduced pressure Particle size D50 / nm PDI 5:1 8mL 25℃ -0.09MPa 122.5 0.097 3:1 6.66mL 15℃ -0.07MPa 114.0 0.098 4:1 7.5mL 20℃ -0.08MPa 159.1 0.163 5:1 8mL 25℃ -0.07MPa 125.9 0.098 3:1 6.66mL 25℃ -0.09MPa 148.4 0.147 4:1 8mL 20℃ -0.08MPa 136.4 0.096 3:1 6.66mL 25℃ -0.07MPa 158.5 0.224 5:1 8mL 15℃ -0.09MPa 113.4 0.113 5:1 8mL 15℃ -0.07MPa 109.2 0.065 3:1 6.66mL 15℃ -0.09MPa 144.7 0.166 4:1 8mL 20℃ -0.08MPa 121.5 0.095

[0079] The above experimental results show that the present invention can prepare a nanomicelle aqueous solution with a particle size D50 between 100 and 250 nm and a PDI between 0.05 and 0.30.

[0080] Example 4 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution of the Present Invention

[0081] Take 15g of the product mPEG-b-PCL in Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of sodium phosphate aqueous solution (aqueous phase, the concentrations of disodium hydrogen phosphate and sodium dihydrogen phosphate in the aqueous phase are 0.05mol / L respectively) under stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%. Add 5.2mL of the above aqueous phase to the micelle solution to prepare a 28% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 185.3nm, the PDI is 0.230, the pH is 6.7, the osmotic pressure is 360mOsm / kg, and in 1s -1 The viscosity at the shear rate is 320 mPa.s.

[0082] Example 5 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution of the Present Invention

[0083] Take 15g of the product mPEG-b-PCL in Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of sodium phosphate aqueous solution (aqueous phase, the concentrations of disodium hydrogen phosphate and sodium dihydrogen phosphate in the aqueous phase are 0.06mol / L respectively) under stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%. Add 11.7mL of the above aqueous phase to the micelle solution to prepare a 25% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 152.0nm, the PDI is 0.193, the pH is 6.8, the osmotic pressure is 321mOsm / kg, and in 1s -1 The viscosity at the shear rate is 92 mPa.s.

[0084] Example 6 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution of the Present Invention

[0085] Take 15g of the product mPEG-b-PCL in Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of sodium phosphate aqueous solution (aqueous phase, the concentrations of disodium hydrogen phosphate and sodium dihydrogen phosphate in the aqueous phase are 0.01mol / L each, and the concentration of sodium chloride is 0.07mol / L) while stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%. Add 5.2mL of the above aqueous phase to the micelle solution to prepare a mPEG-b-PCL nanomicelle aqueous solution with a content of 28% w / w. After testing, the particle size D50 is 180.5nm, the PDI is 0.252, the pH is 6.9, the osmotic pressure is 320mOsm / kg, and the concentration is 1s -1 The viscosity at the shear rate is 726 mPa.s.

[0086] Example 7 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution of the Present Invention

[0087] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of PBS solution (water phase) under stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%. Add 5.2mL of the above aqueous phase to the micelle solution to prepare an mPEG-b-PCL nanomicelle aqueous solution with a content of 28% w / w. After testing, the particle size D50 is 170.7nm, PDI is 0.221, pH is 6.8, osmotic pressure is 360mOsm / kg, and at 1s -1 The viscosity at the shear rate is 880 mPa.s.

[0088] Example 8 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution of the Present Invention

[0089] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of PBS solution (water phase) under stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%. Add 11.7mL of the above aqueous phase to the micelle solution to prepare an mPEG-b-PCL nanomicelle aqueous solution with a content of 25% w / w. After testing, the particle size D50 is 156.7nm, PDI is 0.158, pH is 7.2, osmotic pressure is 353mOsm / kg, and at 1s -1 The viscosity at the shear rate is 207 mPa.s.

[0090] Example 9 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution of the Present Invention

[0091] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of PBS solution (water phase) under stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%. Add 26.7mL of the above aqueous phase to the micelle solution to prepare a 20% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 192.1nm, PDI is 0.277, pH is 7.2, osmotic pressure is 331mOsm / kg, and at 1s -1 The viscosity at the shear rate is 85 mPa.s.

[0092] Example 10 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution of the Present Invention

[0093] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of PBS solution (water phase) under stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%. Add 101.7mL of the above-mentioned aqueous phase to the micelle solution to prepare a 10% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 210.9nm, PDI is 0.289, pH is 7.3, osmotic pressure is 306mOsm / kg, and at 1s -1 The viscosity at the shear rate is 9 mPa.s.

[0094] Example 11 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution of the Present Invention

[0095] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of sodium phosphate aqueous solution (aqueous phase, the concentration of disodium hydrogen phosphate in the aqueous phase is 0.0847mol / L, and the concentration of sodium dihydrogen phosphate is 0.0253mol / L) under stirring. At 20°C, control the pressure to -0.09MPa until the residual acetone is no more than 0.5%, add 5.2mL of the above aqueous phase to the micelle solution, and prepare a 28% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 176.3nm, the PDI is 0.219, the pH is 7.0, and the osmotic pressure is 392mOsm / kg. In 1s -1 The viscosity at the shear rate is 584 mPa.s.

[0096] The beneficial technical effects of the present invention are further illustrated by test examples below.

[0097] Comparative Example 1 Preparation of mPEG-b-PCLA microspheres

[0098] Take 10g of the product mPEG-b-PCLA of Example 1, dissolve it in 40ml of dichloromethane, and add the completely dissolved polymer solution dropwise to a 0.1% w / w PVA aqueous solution. After averaging 1min at a homogenizer speed of 5000rpm, place it under a stirrer and stir for 3 hours. After removing excess dichloromethane, use vacuum filtration to remove the PVA solution, and then freeze-dry to obtain mPEG-b-PCLA microspheres. After testing, the microsphere particle size D50 is 42.2μm and the PDI is 1.670. Use PBS solution to prepare 2% w / w sodium carboxymethylcellulose gel. Before use and testing, add 600mg of microsphere sample to 4mL gel and shake vigorously.

[0099] Comparative Example 2 Preparation of mPEG-b-PCL Nanomicelles Aqueous Solution without Adding Phosphate

[0100] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of purified water (water phase) under stirring. At 20°C, control the pressure to -0.09MPa until the residual acetone is no more than 0.5%. Add 5.2mL of purified water to the micelle solution to prepare an mPEG-b-PCL nanomicelle aqueous solution with a content of 28% w / w. After testing, the particle size D50 is 240.6nm, the PDI is 0.510, the pH is 5.6, and the osmotic pressure is 27mOsm / kg. In 1s -1 The viscosity at the shear rate is 514 mPa.s.

[0101] Comparative Example 3 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution under Other Phosphate Concentration Conditions

[0102] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of sodium phosphate aqueous solution (aqueous phase, the concentration of disodium hydrogen phosphate in the aqueous phase is 0.07mol / L, and the concentration of sodium dihydrogen phosphate is 0.07mol / L) under stirring. At 20°C, control the pressure to -0.09MPa until the residual acetone is no more than 0.5%, add 51.7mL of the above aqueous phase to the micelle solution, and prepare a 15% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 218.1nm, the PDI is 0.342, the pH is 6.8, and the osmotic pressure is 324mOsm / kg. In 1s -1 The viscosity at the shear rate is 95 mPa.s.

[0103] Comparative Example 4 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution under Other Phosphate Concentration Conditions

[0104] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of sodium potassium phosphate aqueous solution (aqueous phase, the concentration of sodium chloride in the aqueous phase is 136.89mmol / L, the concentration of potassium chloride is 2.67mmol / L, the concentration of disodium hydrogen phosphate is 4.05mmol / L, and the concentration of potassium dihydrogen phosphate is 0.88mmol / L) under stirring. At 20°C, control the pressure to -0.09MPa until the residual acetone is no more than 0.5%, add 5.2mL of the above aqueous phase to the micelle solution, and prepare a 28% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 180.5nm, the PDI is 0.257, the pH is 7.0, and the osmotic pressure is 346mOsm / kg. In 1s -1 The viscosity at the shear rate is 30.9 Pa.s.

[0105] Comparative Example 5 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution Using Other Aqueous Phase Systems

[0106] Take 15g of the product mPEG-b-PCL in Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of acetate aqueous solution (aqueous phase, sodium acetate concentration 0.095mol / L, acetic acid concentration 0.0047mol / L) under stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%, add 5.2mL of the above aqueous phase to the micelle solution to prepare a 28% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 174.4nm, the PDI is 0.251, the pH is 6.1, and the osmotic pressure is 265mOsm / kg. In 1s -1 The viscosity at the shear rate is 5.69 Pa.s.

[0107] Comparative Example 6 Preparation of mPEG-b-PCL Nanomicelle Aqueous Solution Using Other Aqueous Phase Systems

[0108] Take 15g of the product mPEG-b-PCL of Example 2 and dissolve it in 100mL of acetone (oil phase), and add 33.3mL of citrate aqueous solution (aqueous phase, sodium citrate concentration 0.095mol / L, citric acid concentration 0.0047mol / L) under stirring. At 20°C, control the pressure to -0.09MPa until the acetone residue is no more than 0.5%, add 5.2mL of the above aqueous phase to the micelle solution to prepare a 28% w / w mPEG-b-PCL nanomicelle aqueous solution. After testing, the particle size D50 is 284.5nm, the PDI is 0.430, the pH is 6.5, and the osmotic pressure is 347mOsm / kg. In 1s -1 The viscosity at the shear rate is 1.26 Pa.s.

[0109] Test Example 1: Syringe handle pushing force and shear viscosity test

[0110] The samples prepared in Example 4 and Comparative Example 1 were drawn with 1 mL prefilled syringes, respectively, using 27G (12 mm long) and 30G (12 mm long) needles, respectively, and the syringe handle pushing forces of the corresponding samples were tested using a microcomputer-controlled electronic universal testing machine.

[0111] Shear viscosity test: 1 mL of the samples prepared in Example 4 and Comparative Example 1 were taken respectively, and the nanomicelle aqueous solution was tested by a rotational rheometer at 1S -1 Shear viscosity at shear rate. Test conditions: 1° cone plate fixture, cone plate fixture diameter 50 mm, test temperature 25°C.

[0112] The test results are as follows:

[0113] Table 2

[0114]

[0115] The experimental results show that the nano-micelle aqueous solution of the present invention has a significantly lower push force when passing through an injection needle of the same size, and can pass through a thinner injection needle, which is beneficial to reducing injection pain and improving injection comfort. On the other hand, the sample prepared in Comparative Example 1 is uneven, and its viscosity cannot even be measured, while the micelle solution of the present invention is uniform, and can effectively reduce the incidence of adverse events such as nodules caused by aggregation when used, and has low viscosity and better diffusivity. It can be seen that the product of the present invention can improve the user experience and enhance safety.

[0116] Test Example 2 Transmission Electron Microscope Analysis

[0117] The sample prepared in Example 4 was diluted to a concentration of 1 mg / mL using a PBS solution, stained with phosphotungstic acid, dried, and analyzed using a transmission electron microscope.

[0118] Transmission electron microscopy images are shown in Figure 1 It can be seen that the product of the present invention is a nano-micelle with uniform particle size (the micelle morphology analysis method can be found in the literature: Micellar Morphologies of Poly(ε-caprolactone)-b-poly(ethyleneoxide)Block Copolymers in Water with a Crystalline Core).

[0119] Test Example 3 Stability Test

[0120] 1. Dilution stability

[0121] Take the samples prepared in Comparative Example 2 and Example 4, and dilute them to 1 mg / mL using their respective corresponding aqueous phase systems. It was observed that flocculent precipitation appeared in Comparative Example 2, while no precipitation appeared in Example 4, indicating that the present invention significantly improves the dilution stability of the product by adding a specific concentration of phosphate. The product of the present invention diffuses in the tissue after injection, and the improvement of dilution stability makes it difficult to precipitate under the dilution condition of tissue fluid. After diffusion, it is conducive to uniform distribution in the tissue, not easy to aggregate and precipitate in situ, and not easy to have local excessive hyperplasia, which is conducive to improving the safety of the product.

[0122] 2. Centrifugal stability

[0123] Take 1 mL of each sample prepared in Comparative Example 2 and Example 4 in a centrifuge tube with a scale, add 1 mL of PBS solution, shake evenly and centrifuge at 2000 rpm for 10 min, take the sample with a scale of 1.5-2 mL in the centrifuge tube and mark it as the upper layer, take the sample with a scale of no more than 0.5 mL in the centrifuge tube and mark it as the lower layer, respectively detect the particle size and compare it with the uncentrifuged sample, the test results are as follows:

[0124] Table 3

[0125]

[0126] The experimental results show that after centrifugation, the particle size and particle size distribution of the upper and lower layers of the sample of Comparative Example 2 are quite different, and precipitation occurs in the lower layer; after centrifugation of the sample of Example 4, there is no obvious difference in the particle size of the upper and lower layers, and no precipitation occurs in the lower layer. It can be seen that the present invention significantly improves the centrifugal stability of the product by adding a specific concentration of phosphate, showing that it has good storage stability, is conducive to maintaining uniformity of the product, can effectively reduce the incidence of adverse events caused by product inhomogeneity, and improve product safety.

[0127] 3. Acceleration stability

[0128] 3.1. The samples prepared in Comparative Examples 2, 4-6, and Examples 5 and 6 were placed in a 40°C stabilization box for accelerated aging, and their pH changes were tested (accelerated aging experiment design reference: YY / T0681.1-2018 "Sterile Medical Device Packaging Test Method Part 1 Accelerated Aging Test Guide", "Guidelines for Registration and Application Materials for Shelf Validity Period of Passive Implantable Medical Devices"). The test results are as follows:

[0129] Table 4

[0130]

[0131] Note: The conventional storage conditions for the product of the present invention are refrigeration at 2-8°C, and accelerated aging at 40°C for 17 days, 25 days, 33 days, and 65 days are equivalent to aging for 6 months, 9 months, 12 months, and 24 months under conventional storage conditions, respectively.

[0132] The experimental results show that the pH of the sample of Comparative Example 2 without the addition of phosphate changes significantly in the accelerated aging experiment, posing a potential safety hazard in use.

[0133] Comparative Examples 5 and 6 used other aqueous phase systems to prepare nanomicelle aqueous solutions. As a result, the pH of Comparative Example 5 changed significantly in the accelerated aging experiment; although the pH change of Comparative Example 6 was not large, the particle size distribution uniformity of the prepared nanomicelles was poor and the particle size was also relatively large.

[0134] In Comparative Example 4, the pH dropped significantly in the accelerated aging experiment due to insufficient concentration of added phosphate.

[0135] In contrast, the pH of the samples in Example 5 and Example 6 hardly changed after accelerated aging for 65 days (equivalent to aging for 24 months under normal storage conditions), indicating that the addition of a specific concentration of phosphate to the nanomicelle aqueous solution of the present invention can ensure the stability of the product, and the prepared nanomicelles have uniform particle size distribution and small particle size.

[0136] 3.2. The samples prepared in Comparative Example 3, Examples 4, and 6 to 8 were placed in a 60°C oven to test their osmotic pressure changes. The test results are as follows:

[0137] Table 5

[0138] Comparative Example 3 Example 4 Example 6 Example 7 Example 8 Total phosphate concentration in the aqueous phase 0.14mol / L 0.10mol / L 0.02mol / L 9.86mmol / L 9.86mmol / L Initial osmotic pressure 324mOsm / kg 360 mOsm / kg 320mOsm / kg 360 mOsm / kg 353mOsm / kg 7-day osmotic pressure 353mOsm / kg 379mOsm / kg 328mOsm / kg 372mOsm / kg 362mOsm / kg Osmotic pressure increase 29mOsm / kg 19mOsm / kg 8mOsm / kg 12mOsm / kg 9mOsm / kg

[0139] As can be seen from Table 5, when the accelerated test was carried out at 60°C, the osmotic pressure of the samples of Examples 4, 6 to 8 changed little; while in Comparative Example 3, the concentration of phosphate added was too high, and the osmotic pressure of the sample showed a trend of rapid increase under the same accelerated test conditions. It can be seen that the phosphate concentration has a significant effect on the stability of the nanomicelle aqueous solution of the present invention.

[0140] Test Example 4 Tissue reaction after injection of the nanomicelle aqueous solution of the present invention

[0141] In order to demonstrate the advantages of the nano-micelle aqueous solution of the present invention in terms of dispersibility, tissue compatibility, adverse reactions, regeneration and filling effects, the following animal experiments were conducted.

[0142] Six SD rats weighing 250g at 6 to 8 weeks old were selected as experimental animals. PBS solution, the nanomicelle product of Example 4 and the microsphere product of Comparative Example 1 were selected for the experiment. The sample in Comparative Example 1 needs to be shaken vigorously before injection and injected quickly using a 23G needle. Injection method: Different samples are injected into every 3 rats, with 4 injection sites on the back of each rat, subcutaneous single-point injection, 0.2mL injected at each site, and each sample is repeatedly injected into two rats, and the injection sites are marked with a non-fading marker. During the experiment, the feeding environment was set to a temperature of 24°C, a relative humidity of 50% and a lighting time of 12 hours, and free food was available.

[0143] The experimental animals were killed after 13 weeks. Skin tissues of the three groups of samples were obtained according to the injection mark positions. The animal anatomical structures corresponding to the three samples are as follows: Figure 2 As shown. After injection, the filler of the sample of comparative example 1 can be peeled off from the skin. The filler and PBS solution, and the skin tissue of the sample of example 4 are fixed with a neutral 10% formalin solution, embedded and solidified with paraffin, and slices are prepared. The slices are stained with hematoxylin and eosin (HE) and Masson's Trichrome to observe the inflammatory response and the effect of promoting collagen regeneration. The tissue is observed using an optical microscope, and the results are as follows Figure 3 and Figure 4 shown.

[0144] from Figure 2 It can be seen that after the injection of the sample of Example 4 and the sample of Comparative Example 1, the dispersion area of ​​the sample of Example 4 is larger than that of the sample of Comparative Example 1, and the sample of Comparative Example 1 aggregates in vivo, indicating that the sample prepared by Example 4 has better dispersibility. In addition, after the injection of the sample of Comparative Example 1, the filler can be peeled off from the skin, while the sample of Example 4 has good tissue compatibility and cannot be peeled off from the skin (e.g. Figure 2 The right side section is shown in the enlarged part). Further combined with the HE staining image ( Figure 3 ) It can be seen that after implantation, the sample of comparative example 1 peeled off an irregularly shaped wrapping, while after implantation of the sample of example 4, no boundary between the filler and the skin tissue could be observed on the HE staining image, and the skin thickness was uniform (the blue arrow in the figure indicates the skin thickness at the filling position), which is consistent with Figure 2 The anatomical structure of Figure 2 and Figure 3 , showing that the sample of Example 4 is more evenly dispersed than that of Comparative Example 1 and has better tissue compatibility.

[0145] Figure 3The results show that: on the one hand, compared with the PBS solution, no significant inflammatory reaction was observed after the implantation of the sample of Example 4; lymphocytes, macrophages and giant cells were observed after the implantation of the sample of Comparative Example 1, indicating that the inflammatory reaction caused by the sample of Comparative Example 1 was stronger than that caused by the sample of Example 4. On the other hand, after the injection of the sample of Example 4, the skin thickness increased ( Figure 3 The width of the blue double arrow mark is the subcutaneous thickness), and collagen was detected in the sample site, indicating that the nanomicelles of the present invention have the regenerative ability to stimulate the body to produce collagen and can play a filling role. The regenerative material is prepared into a nanomicelle aqueous solution by the technology of the present invention without affecting its regenerative ability.

[0146] from Figure 4 It can be seen that the collagen produced after using the sample of Comparative Example 1 is a disordered structure, filling the entire filler, while the collagen produced by the sample of Example 4 is an ordered structure. It can be seen that the probability of scarring in the sample of Comparative Example 1 is higher than that in the sample of Example 4.

[0147] Based on the above experimental results, the nano-micelle aqueous solution of the present invention has good dispersibility, better tissue compatibility, low probability of adverse reactions such as inflammatory reactions and scars, and has regeneration and filling capabilities.

[0148] Test Example 5 Safety Evaluation of the Nanomicelle Aqueous Solution of the Present Invention

[0149] In order to further evaluate the safety of the nano-micelle aqueous solution of the present invention, samples prepared in Comparative Example 2, Example 5 and Example 7 were respectively taken to carry out animal intradermal reaction experiments and gross observations after implantation.

[0150] 1. Animal intradermal reaction test

[0151] The evaluation was carried out according to GB16886.10-2017, and the results are as follows:

[0152] Table 6

[0153] Comparative Example 2 Example 5 Example 7 Score 2.67 0.09 0 Result (not greater than 1) Failure qualified qualified

[0154] According to Part 10 of the Biological Evaluation of Medical Devices in GB16886.10-2017, the animal intradermal reaction experiment in the stimulation and skin sensitization experiment, the reaction (erythema and eschar, edema) score shall not be greater than 1, otherwise there is a safety risk for human use. As can be seen from Table 6, among the test samples, the intradermal reaction score of Comparative Example 2 is the highest and far greater than 1, while the nanomicelle aqueous solution of Examples 5 and 7 of the present invention has a score of almost 0, showing its high safety. The above experimental results show that the present invention adds a specific concentration of phosphate in the nanomicelle aqueous solution, which is beneficial to improve the safety of the product.

[0155] 2. General observation after implantation

[0156] Based on the results of the animal intradermal reaction experiment, the safety of the samples of Comparative Example 2 and Example 7 was further compared. Six SD rats weighing 250 g and aged 6 to 8 weeks were selected as experimental animals. The PBS solution, the samples prepared in Comparative Example 2 and Example 7 were respectively taken for experiments. Injection method: 4 samples were injected into each rat at the same time, and 4 injection sites were located on the back of each rat (the samples corresponding to each injection site were as follows Figure 5 and Figure 6 The experimental animals were sacrificed after 1 week. The rat skin tissue was observed and photographed after dissection. The dissection diagram is shown in Figure 5 and Figure 6 .

[0157] contrast Figure 5 and Figure 6 It can be clearly seen that: one week after the implantation of the sample of Comparative Example 2, obvious abnormalities appeared in the three animals, while no abnormalities were found after the implantation of the sample of Example 7, and no wrapping was formed, indicating that the sample of Example 7 has good compatibility with the surrounding tissues.

[0158] Combining the intradermal reaction data and the subcutaneous implantation data, it can be seen that the nano-micelle solution of the present invention has high safety.

[0159] Test Example 6 Evaluation of the effectiveness of the nanomicelle aqueous solution of the present invention

[0160] In order to demonstrate the effectiveness of the nanomicelle aqueous solution with different contents in the present invention in terms of filling effect, the following animal experiment was conducted.

[0161] Eight SD rats weighing 250g and aged 6 to 8 weeks were selected as experimental animals. PBS solution and the nanomicelle products of Examples 7 to 10 were selected for the experiment. Injection method: PBS and one sample of the example were injected into each rat at the same time. Two rats were grouped together, and each rat was injected at four injection sites on the back. Single subcutaneous injection was performed, and 0.2 mL was injected at each site. The injection site was marked with a non-fading marker pen. The injection method was as follows: Figure 7 During the experiment, the feeding environment was set at a temperature of 24°C, a relative humidity of 50% and a lighting period of 12 hours, and the animals were allowed to eat freely.

[0162] The experimental animals were killed after 13 weeks, and the injection sites after dissection were observed and photographed under the light of the LED panel. The animal anatomical structures corresponding to each experimental sample are as follows: Figure 7As shown. Obtain the skin tissue of the injection group sample according to the injection mark position. The skin tissue of the sample was fixed with a neutral 10% formalin solution, embedded and solidified with paraffin, and slices were prepared. The slices were stained with hematoxylin and eosin (HE). Use an optical microscope to take pictures, select the field of view of the entire tissue sample, measure the skin thickness at the filling position, select 10 sites that are relatively uniform, and take the average value, as shown in Figure 1. Figure 8 to Figure 12 shown.

[0163] from Figure 7 It can be seen that at 13 weeks, the implantation sites of the samples of Examples 7 to 10 were obviously different from the implantation sites of PBS, showing a physical space-occupying effect. Figure 8 to Figure 12 The tissue thickness measurement diagrams corresponding to PBS and samples of Examples 7 to 10 after implantation are respectively: the average values ​​are: 105.1 μm, 1735.7 μm, 1571.5 μm, 1294.5 μm and 570.4 μm, and the relative standard deviations RSD are: 0.37, 0.06, 0.14, 0.04 and 0.19. The average values ​​reflect that the samples of Examples 7 to 10 significantly increase the tissue thickness of the implanted parts; the RSD reflects that the skin thickness after injection of the samples of Examples 7 to 10 is more uniform than that after injection of PBS, which further reflects the dispersion uniformity of the nanomicelle aqueous solution of the present invention.

[0164] It should be noted that the specific features, structures, materials or characteristics described in this specification may be combined in any one or more embodiments in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments and features of the different embodiments described in this specification without contradiction.

Claims

1. An aqueous solution of mPEG-modified polyester material for collagen regeneration, characterized in that: The mPEG modified polyester material is selected from at least one of mPEG-b-PCL and mPEG-b-PCLA; the content of the mPEG modified polyester material in the aqueous solution is 20-28% w / w, and contains phosphate with a concentration of 9.86 mmol / L-0.12 mol / L; the phosphate consists of monohydrogen phosphate and dihydrogen phosphate, wherein the molar ratio of monohydrogen phosphate: dihydrogen phosphate is 1:(0.19-1.67).

2. The aqueous solution according to claim 1, characterized in that: Contains phosphate at a concentration of 9.86mmol / L or 0.12mol / L.

3. The aqueous solution as claimed in claim 1 or 2, wherein the phosphoric acid The molar ratio of monohydrogen salt: dihydrogen phosphate is 4.6:1 or 1:

1.

4. The aqueous solution as claimed in claim 3, characterized in that: The monohydrogen phosphate is at least one of disodium hydrogen phosphate and dipotassium hydrogen phosphate; and / or the dihydrogen phosphate is at least one of sodium dihydrogen phosphate and potassium dihydrogen phosphate.

5. The aqueous solution according to claim 1, characterized in that: The phosphate consists of 0.06 mol / L disodium hydrogen phosphate and 0.06 mol / L sodium dihydrogen phosphate, or consists of 8.1 mmol / L disodium hydrogen phosphate and 1.76 mmol / L potassium dihydrogen phosphate.

6. The aqueous solution according to claim 1, characterized in that: Where m The content of the PEG-modified polyester material is 20-25% w / w.

7. The aqueous solution according to claim 1, characterized in that: Where m PEG-modified polyester materials are nano-micelles.

8. The aqueous solution as claimed in claim 7, characterized in that: The particle size D50 of the nano micelles is 10 to 500 nm; preferably, the particle size D50 of the nano micelles is 100 nm to 250 nm.

9. The aqueous solution as claimed in claim 7, characterized in that: The particle size distribution PDI of the nano micelles is 0.05 to 0.40; preferably, the particle size distribution PDI of the nano micelles is 0.05 to 0.

30.

10. The aqueous solution according to claim 1, characterized in that: The pH value is 5 to 8; preferably, the pH value is 6.7 to 7.

3.

11. The aqueous solution according to claim 1, characterized in that: Viscosity: 5~3000mPa . S; preferably, the viscosity is 5 to 1000 mPa . S; preferably, the viscosity is 50 to 1000 mPa . S.

12. The aqueous solution according to claim 1, characterized in that: The osmotic pressure is 200 to 450 mOsm / kg; preferably, the osmotic pressure is 300 to 400 mOsm / kg.

13. The aqueous solution according to claim 1, characterized in that: It also contains an osmotic pressure regulator; preferably, the osmotic pressure regulator is selected from at least one of sodium chloride, potassium chloride and glycerol.

14. The aqueous solution according to claim 1, characterized in that: The molecular weight of mPEG in the mPEG-modified polyester material is 500 to 20,000 Daltons; preferably, the molecular weight of mPEG in the mPEG-modified polyester material is 1,900 to 10,000 Daltons; preferably, the molecular weight of mPEG in the mPEG-modified polyester material is 1,900 to 5,000 Daltons.

15. The aqueous solution according to claim 1, characterized in that: The mass percentage of mPEG in the mPEG-modified polyester material is 5% to 50%; preferably, the mass percentage of mPEG in the mPEG-modified polyester material is 7% to 26%.

16. The aqueous solution according to any one of claims 1 to 15, characterized in that: It is an injection form.

17. Use of the aqueous solution according to any one of claims 1 to 16 in the preparation of a tissue repair product.

18. Use of the aqueous solution according to any one of claims 1 to 16 in the preparation of a dermal filling product.

19. Use of the aqueous solution according to any one of claims 1 to 16 in the preparation of collagen regeneration products.

20. The method for preparing the aqueous solution according to any one of claims 1 to 16, characterized in that: The organic solvent evaporation method was used.

Citation Information

Patent Citations

  • Polycaprolactone microsphere pre-dispersion composition and polycaprolactone injection gel prepared from same

    CN115282337A

Cited By

  • Tissue filler for injection and preparation method thereof

    CN120939288A